Estratégia de gerenciamento energético consciente da degradação das baterias de veículos elétricos em estacionamentos inteligentes - Sausen, Jordan Passinato (2022)
The combination of electric vehicles bidirectional characteristic along with distributed energy resources follows a trend in energy management strategies. However, additional charging and discharging cycles, treated here together as dis/charging, intensifies the wear on batteries. In this context, this thesis proposes the development of a systemic energy management model for a smart parking lot. The day ahead scheduling is determined as a function of priorities, tariff signals, and battery degradation. As an innovative aspect of this research, the introduction of wear functions is proposed, deriving a degradation index as one of the problem guidelines. The nature of the model input parameters is approached in a deterministic way, estimated from a statistical analysis of parking occupancy pattern and energy profile. Direct charging strategy and different parking lot configurations constitute case studies aimed at confronting the proposed strategy under different occupancy scenarios and energy management techniques. The results demonstrate that maximizing the dis/charging rates satisfies electric vehicles energy needs, and reduces charging costs and EV battery degradation through optimal power dispatch. It is proven that is possible to reduce the parking lot overall operational cost by over 50% by a battery conscious strategy when used in bidirectional energy exchanges. The charging schedule is designed to reduce the impact on the batteries while reducing the cost equivalent to compensation for degradation.